Effective Use of Water in Crop Plants in Dryland Agriculture: Implications of Reactive Oxygen Species and Antioxidative System - Rane, Jagadish; Singh, Ajay Kumar; Tiwari, Manish; Prasad, P. V. Vara; Jagadish, S. V. Krishna (Frontiers in Plant Science, 2022)
Under dryland conditions, both annual and perennial food crops are exposed to dry spells, which severely affect crop productivity by limiting available soil moisture at critical and sensitive growth stages. The variable climate continues to be the major cause of uncertainty, often making timing rather than quantity of precipitation the foremost concern. Mitigation and management of stress experienced by plants due to limited soil moisture is crucial for sustaining crop productivity under current and future harsher environments. Hence, information generated so far through multiple investigations on mechanisms inducing drought tolerance in plants needs to be translated into tools and techniques for stress management. Scope to accomplish this exists in inherent capacity of plants to manage stress at cellular level through various mechanisms. One of the most extensively studied but yet not conclusive physiological phenomenon is the balance between Reactive Oxygen Species (ROS) production and scavenging through Antioxidative System (AOS), which reflects in a wide range of damage to the cell, organ and the plant. In this context, this review aims to examine possible roles of ROS-AOS balance in enhancing effective use of water (EUW) by crops under water limited dryland conditions. We refer EUW as biomass produced by plant with available water under soil moisture stress, rather than per unit of water (WUE). We hypothesize that EUW can be enhanced by an appropriate balance between water saving and growth promotion at whole plant level during stress and post-stress recovery periods. The ROS-AOS interactions have a key role to play in water saving mechanisms and biomass accumulation resulting from growth processes that include cell division, cell expansion, photosynthesis and translocation of assimilates. Hence, appropriate strategies for manipulating these processes through genetic improvement and/or use of exogenous compounds can provide practical solutions for improving EUW through optimized ROS-AOS balance under water limited dryland conditions. This review deals with role of ROS-AOS in two major EUW determining processes namely water use and plant growth process. This review also describes implications of ROS level or content, ROS-producing and ROS-scavenging enzymes on plant water status which ultimately affects photosynthetic efficiency and growth of plants.